The effect of obesity on functional capacity, anxiety and daily life activities in patients with coronary artery disease and phase II cardiac rehabilitation - Kasapoğlu Aksoy, Meliha; Aykurt Karlıbel, İlknur and Arı, Hasan and Altan, Lale (The European Research Journal, 2018)
Objective. The aim of our study was to investigate the effect of cardiac rehabilitation (CR) program on obese and non-obese patients with coronary artery disease. Methods. The records of 60 coronary artery disease patients aged between 18-75 years, who were included in CR were evaluated. Of the study subjects, 20 had undergone coronary artery bypass grafting (CABG) and 40 had undergone percutaneous coronary intervention (PCI). The patients were divided into two groups by body mass index (BMI), with Group I being non-obese (BMI < 30 kg/m2) and Group 2 being obese (BMI ≥ 30 kg/m2). The effect of 30 session CR on the two groups were evaluated with 6-min walk test (6MWT), Short Form-36 (SF-36) and Beck Anxiety Inventory (BAI). Results. Baseline characteristics of the group 1 (39 patients) and group 2 (21 patients) were similar. Statistically significant improvement was detected in group 1 and group 2 patients by CR program in 6MWT, BAI and SF-36 parameters (p < 0.05). 6MWT, BAI and SF-36 parameters changes by cardiac rehabilitation were compared between the two groups. According to the comparison 6MWT (group 1; 60 (20-183) vs group 2; 34 (15-180), p = 0.012) and MET (group 1; 1.44 ± 0.56 vs group 2; 1.09 ± 0.41, p = 0.015 changes were significantly higher in group 1 than in group 2. However, the changes of BAI and SF-36 parameters were similar in two groups (p > 0.05). Conclusion. CR was found to be effective and safe in terms of functional capacity, daily life activities and anxiety in both obese and non-obese patients. Functional capacity gain in the obese group was less than non-obese patients.